please show your work

Community Answer

Honor CodeSolved 2 Answers

See More Answers for FREE

Enhance your learning with StudyX

Receive support from our dedicated community users and experts

See up to 20 answers per week for free

Experience reliable customer service

Get Started

(a) \dot{y}-2 \dot{y}+y=2 u\omega . K . T\begin{array}{l}x^{0}=A x+B U \\y=C x+D U\end{array}D= feed forward component, leads to instability, usually 'Zero'foluStept: Transfer lower order terms to RHS\dot{y}=-y+2 \dot{y}+2 uStep-2: State variables: State variables must be linearly independent of other state variables\Rightarrow we can use derivatives of state variable as thry are not linearly dependent on each other\therefore \quad y=x_{1}then \quad \dot{y}=x_{1}^{0}=x_{2}y=x_{2}Replacing terms in eq (1) with state variables ' x '\begin{array}{l}\Rightarrow \quad x_{1}^{0}=x_{2} \\y=x \\x_{2}^{0}=-x_{1}+2 x_{2}+2 u \\\end{array}In matsix form\begin{aligned}{\left[\begin{array}{l}x_{1}^{0} \\\dot{x}_{2}\end{array}\right] } & =\left[\begin{array}{ll}0 & 1 \\-1 & 2\end{array}\right]\left[\begin{array}{l}x_{1} \\x_{2}\end{array}\right]+\left[\begin{array}{l}0 \\2\end{array}\right] U \\y & =\left[\begin{array}{ll}1 & 0\end{array}\right]\left[\begin{array}{l}x_{1} \\x_{2}\end{array}\right]+[0] U\end{aligned}\xi(b)\text { b) } \begin{array}{r}\quad y-3 y^{0 .}+2 y^{0}-\dot{y}-y=3 u \\w \cdot k-7 \quad x=A x+B u \\y=c x+D u \\\Rightarrow \quad y=y+\dot{y}-2 \ddot{y}+3 \ddot{y}+3 u\end{array}(tolloning previous steps)\begin{aligned}y & =x_{1} \\\dot{y} & =\dot{x}_{1}=x_{2} \\\ddot{y}^{\prime} & =\dot{x}_{2}=x_{3} \\\dot{y}^{0} & =\dot{x}_{3}=x_{4} \\y_{0} & =\dot{x}_{4} \\\dot{y}_{1} & =x_{2} \\\dot{x}_{2} & =x_{3} \\\dot{x}_{3} & =x_{4} \\\dot{x}_{4} & =x_{1}+x_{2}-2 x_{3}+3 x_{4}+3 u\end{aligned}y=x_{1}In Mataix form\begin{array}{l}\text { In Matsix form } \\{\left[\begin{array}{l}0 \\x_{1} \\\dot{x}_{2} \\\dot{x}_{3} \\\dot{x}_{4}\end{array}\right]=\left[\begin{array}{llll}0 & 1 & 0 & 0 \\0 & 0 & 1 & 0 \\0 & 0 & 0 & 1 \\1 & 1 & -2 & 3\end{array}\right]\left[\begin{array}{l}x_{1} \\x_{2} \\x_{3} \\x_{4}\end{array}\right]+\left[\begin{array}{l}0 \\0 \\0 \\3\end{array}\right] \cup\left[\begin{array}{l}x_{1} \\x_{2} \\x_{3} \\x_{4}\end{array}\right]+[0] U}\end{array}Care should be taken while representing in final matrix form.  The value of D - feed forward component is not always zero, it's value depends on  ...